2022
DOI: 10.3390/antiox11030460
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of SOD and GPX Gene Families in the Soybeans in Response to Drought and Salinity Stresses

Abstract: Plant stresses causing accumulation of reactive oxidative species (ROS) are scavenged by effective antioxidant defense systems. Therefore, the present study performed genome-wide identification of superoxide dismutase (SOD) and glutathione peroxidase (GPX) gene families in cultivated and wild soybeans, and 11 other legume species. We identified a total of 101 and 95 genes of SOD and GPX, respectively, across thirteen legume species. The highest numbers of SODs and GPXs were identified in cultivated (Glycine ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…Phylogenetic studies of GPX genes from different plant species showed that their number varies between 2 and 25 [ 39 , 40 , 41 ]. For example, two GPX genes were identified in Physcomitrella patens [ 39 ] and Panax ginseng [ 42 ], three in Hordeum vulgare [ 43 ] and Vigna radiata [ 44 ], four in Pinus tabulaeformis [ 45 ] and Brachypodium distachyon [ 39 ], and five genes in Oryza sativa [ 16 , 39 ], Phoenix dactylifera (date palm) [ 46 ], Populus trichocarpa [ 26 ], Ricinus communis [ 47 ], and Solanum lycopersicum [ 39 ]. Six GPXs are encoded by Cucumis sativus [ 48 ], Citrullus lanatus [ 49 ] and Lotus japonica [ 50 ] genome, seven genes were found in Sorghum bicolor [ 51 ] and Zea mays [ 52 ], while there are eight in Arabidopsis thaliana [ 53 ] and Brassica oleracea [ 40 ].…”
Section: Phylogenetic Aspects Of Plant Gpxsmentioning
confidence: 99%
See 4 more Smart Citations
“…Phylogenetic studies of GPX genes from different plant species showed that their number varies between 2 and 25 [ 39 , 40 , 41 ]. For example, two GPX genes were identified in Physcomitrella patens [ 39 ] and Panax ginseng [ 42 ], three in Hordeum vulgare [ 43 ] and Vigna radiata [ 44 ], four in Pinus tabulaeformis [ 45 ] and Brachypodium distachyon [ 39 ], and five genes in Oryza sativa [ 16 , 39 ], Phoenix dactylifera (date palm) [ 46 ], Populus trichocarpa [ 26 ], Ricinus communis [ 47 ], and Solanum lycopersicum [ 39 ]. Six GPXs are encoded by Cucumis sativus [ 48 ], Citrullus lanatus [ 49 ] and Lotus japonica [ 50 ] genome, seven genes were found in Sorghum bicolor [ 51 ] and Zea mays [ 52 ], while there are eight in Arabidopsis thaliana [ 53 ] and Brassica oleracea [ 40 ].…”
Section: Phylogenetic Aspects Of Plant Gpxsmentioning
confidence: 99%
“…In most of the cases, a relatively higher number of GPX genes was found in plants with polyploid genome [ 54 ]. For example, 12 genes were identified in Brassica rapa [ 40 ] and Triticum aestivum [ 55 ], 13 in Gossypium hirsutum [ 54 ] and Glycine max [ 44 ], and 25 GPX genes in Brassica napus [ 40 ].…”
Section: Phylogenetic Aspects Of Plant Gpxsmentioning
confidence: 99%
See 3 more Smart Citations